A COMPLEXA RELAÇÃO ENTRE DEMOCRACIA E LEGITIMIDADE - Gonçalves Gomes, Reginaldo (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2025)
This article explores the complex relationship between democracy and legitimacy, highlighting the perceived duality among philosophers. Philosophers warn of the threat of totalitarianism, which seeks to fill this void and deny the indeterminacy of political modernity. Democracy is always susceptible to this danger, requiring a constant interpretation of society in political terms to preserve the people's freedom. They echo contemporary warnings about the importance of continuous vigilance to protect democratic institutions. They emphasize that initiatives to subvert democracy often disguise themselves under the guise of legality and public objectives, demanding constant attention to prevent the gradual weakening of democratic institutions. Furthermore, legitimacy for the exercise of power and the legitimacy of decisions in a complex society are discussed. Different theoretical perspectives on the legitimacy of power are explored, addressing topics such as domination, economic power, democratic legitimacy, and models of deliberation, presenting criticisms of deliberative democracy.